2013
DOI: 10.1111/imm.12062
|View full text |Cite
|
Sign up to set email alerts
|

CD40 ligand and interferon‐γ induce an antimicrobial response against Mycobacterium tuberculosis in human monocytes

Abstract: SummaryThe ability of T cells to activate antimicrobial pathways in infected macrophages is essential to host defence against many intracellular pathogens. Here, we compared the ability of two T-cell-mediated mechanisms to trigger antimicrobial responses against Mycobacterium tuberculosis in humans, CD40 activation and the release of interferon-c (IFN-c). Given that IFN-c activates a vitamin D-dependent antimicrobial response, we focused on induction of the key components of this pathway. We show that activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 38 publications
(82 reference statements)
5
60
0
Order By: Relevance
“…This suggests that interactions between activated T cells and macrophages might induce mechanisms that allow efficient conversion of 25(OH)D 3 to 1,25(OH) 2 D 3 in vivo despite the presence of DBP. This is in good accordance with previous studies which found that treatment of macrophages with IFN-γ or soluble CD40L increases their expression of CYP27B1 and their capacity to convert 25(OH)D 3 to 1,25(OH) 2 D 3 [59-61]. Thus, whether vitamin D actually affects a given T cell response in vivo probably relies on a mixture of factors in addition to the concentration of 25(OH)D 3 such as the isotype, local concentration and degradation rate of DBP and the expression levels of CYP27B1, the VDR and the 1,25(OH) 2 D 3 -24-hydroxylase CYP24A1 of the cells locally involved in the immune response.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that interactions between activated T cells and macrophages might induce mechanisms that allow efficient conversion of 25(OH)D 3 to 1,25(OH) 2 D 3 in vivo despite the presence of DBP. This is in good accordance with previous studies which found that treatment of macrophages with IFN-γ or soluble CD40L increases their expression of CYP27B1 and their capacity to convert 25(OH)D 3 to 1,25(OH) 2 D 3 [59-61]. Thus, whether vitamin D actually affects a given T cell response in vivo probably relies on a mixture of factors in addition to the concentration of 25(OH)D 3 such as the isotype, local concentration and degradation rate of DBP and the expression levels of CYP27B1, the VDR and the 1,25(OH) 2 D 3 -24-hydroxylase CYP24A1 of the cells locally involved in the immune response.…”
Section: Discussionsupporting
confidence: 93%
“…This leads us to speculate that VDR agonists could be used therapeutically to increase cathelicidin production in TAMs and enhance their cytotoxic activity in vivo. It is worth noting that the expression of cathelicidin is also up-regulated by mycobacterial antigens, interferon-g (12), and CD40 ligand (40) in human macrophages. Recent studies also indicate that macrophage tumoricidal activity could be therapeutically enhanced upon administration of live mycobacterium Bacille Calmette-Guérin (41), muramyl tripeptide (42), or CD40 agonistic antibodies (2).…”
Section: Discussionmentioning
confidence: 99%
“…Today we recognize that autophagy is widely integrated with immunity starting from cell-autonomous defense against invading bacteria and viruses to regulation of innate and adaptive immunity in general ). The initial observations uncovering the role of autophagy against M. tuberculosis (Gutierrez et al 2004;Singh et al 2006) have been followed by a gradual increase in studies supporting and extending these early findings (Alonso et al 2007;Harris et al 2007;Xu et al 2007;Biswas et al 2008;Jagannath et al 2009;Yuk et al 2009;Ghadimi et al 2010;Kumar et al 2010;Ponpuak et al 2010;Shin et al 2010b;Singh et al 2010;Fabri et al 2011a,b;Campbell and Spector 2012;Juarez et al 2012;Petruccioli et al 2012;Watson et al 2012;Zullo and Lee 2012;Anandaiah et al 2013;Klug-Micu et al 2013;Manzanillo et al 2013). In this article we briefly cover autophagy as a pathway and its broad roles in immunity and summarize what has been learned about autophagy in tuberculosis thus far.…”
mentioning
confidence: 93%